Pengaruh CAR, BOPO, dan FDR Terhadap NPF Pada Bank Syariah Indonesia Periode Tahun 2016-2021 - Annisa Rahayu; Fazhar Sumantri; Feby Angriawan Latumanase; Danni Maulana; Aditya Prasetyo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Islamic bank is a banking system that runs a system of financial activities based on Islamic law. The performance of Islamic banks can be measured by the size of the NPF. Factors that affect NPF basically come from outside and inside the company such as CAR, BOPO, and FDR. This study aims to examine the effect of Non Performing Financing (NPF) from Islamic banks with the Capital Adequacy Ratio (CAR), Operating Costs and Operating Income (BOPO) and Financing to Deposit Ratio (FDR). This research is a quantitative research. The data used is quarterly data at BRI Syariah Bank. In this study using multiple regression data analysis. The classical assumption tests used in this research are normality, multicollinearity, heteroscedasticity and autocorrelation. The research shows that NPF has a positive and significant effect on CAR, BOPO, and FDR. The predictive capability of the three variables on the NPF is 56.6%, while the rest are affected by other factors outside the research model